Atropisomerism in Diarylamines: Structural Requirements and Mechanisms of Conformational Interconversion. (20th August 2020) - Costil, Romain; Sterling, Alistair J.; Duarte, Fernanda; Clayden, Jonathan
Abstract: In common with other hindered structures containing two aromatic rings linked by a short tether, diarylamines may exhibit atropisomerism (chirality due to restricted rotation). Previous examples have principally been tertiary amines, especially those with cyclic scaffolds. Little is known of the structural requirement for atropisomerism in structurally simpler secondary and acyclic diarylamines. In this paper we describe a systematic study of a series of acyclic secondary diarylamines, and we quantify the degree of steric hindrance in the ortho positions that is required for atropisomerism to result. Through a detailed experimental and computational analysis, the role of each ortho ‐substituent on the mechanism and rate of conformational interconversion is rationalised. We also present a simple predictive model for the design of configurationally stable secondary diarylamines. Abstract : Hindered secondary diarylamines Ar 1 NHAr 2 can show chirality due to restricted rotation about their C−N bonds. Using a combination of dynamic analytical methods and computational models, we describe the requirements for atropisomerism in these diarylamines and provide a model for estimating their barrier to interconversion.